Life-cycle thinking and performance-based design of bridges: A state-of-the-art review - Alaa Al Hawarneh; M. Shahria Alam; Rajeev Ruparathna; Stavroula J. Pantazopoulou (Resilient Cities and Structures, 2025)
Given the growing emphasis on life-cycle analysis in bridge design, the design community is transitioning from the concept of performance-based design in structural engineering to a performance-based design approach within a life-cycle context. This approach considers various indicators, including cost, environmental impact, and societal factors when designing bridges. This shift enables a comprehensive assessment of structural resilience by examining the bridge's ability to endure various hazards throughout its lifespan. This study provides a comprehensive review of two key research domains that have emerged in the field of bridge life-cycle analysis, namely life-cycle sustainability (LCS) and life-cycle performance (LCP). The discussion on the LCS of bridges encompasses both assessment-based and optimization-based studies, while the exploration of LCP focuses on research examining structures subjected to deterioration over their service life due to deprecating phenomena such as corrosion and relative humidity changes, as well as extreme hazards like earthquakes and floods. Moreover, this study discusses the integration between LCS and LCP, highlighting how combined consideration of these factors can minimize damage costs, improve resiliency, and extend the lifespan of the structure. A detailed evaluation encompasses various life-cycle metrics, structural performance indicators, time-dependent modelling techniques, and analysis methods proposed in the literature. Additionally, the research identifies critical gaps and trends in life-cycle analysis within the realm of bridge engineering, providing a concise yet thorough overview for advancing considerations in the life-cycle design of bridges.